Magnitude e tendência da Leishmaniose Tegumentar Americana no Estado de São Paulo, Brasil, 1975 a 2008 Magnitude and trend of American Tegumentary Leishmaniasis in the State of São Paulo, Brazil, 1975 to 2008 - Rubens Antonio da Silva; Vanessa Taís Cruz Mercado; Lúcia de Fátima Henriques; Ricardo Mário de Carvalho Ciaravolo; Dalva Marli Valério Wanderley (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2012)
O objetivo deste estudo foi analisar a magnitude e tendência da Leishmaniose Tegumentar Americana (LTA) no Estado de São Paulo entre 1975 e 2008. Foi conduzido um estudo ecológico que categorizou os municípios segundo a magnitude da transmissão. No período de 1975 a 1985, 45 municípios foram responsáveis pelo registro de 1.281 casos de LTA, passando a 258 municípios e 4.093 casos entre 1986 e 1995, e a 385 municípios e 7.604 casos entre 1996 a 2008. O vetor Lutzomyia intermedia s.l. foi coletado na maioria das pesquisas entomológicas. Na classificação dos municípios segundo a magnitude pode-se verificar que 67,5% possuíam "pequena magnitude", 19,2% "média magnitude" e 13,3% "grande magnitude". As maiores incidências de LTA permanecem restritas a algumas áreas carentes e próximas à Mata Atlântica. Houve aumento no número de municípios com pequena ocorrência de casos e ampliação da área de risco. The aim of this study was to analyze the magnitude and trend of American Tegumentary Leishmaniasis (ATL) in the State of São Paulo from 1975 to 2008. An ecological study that classified municipalities according to the magnitude of transmission was performed. From 1975 to 1985, 1,281 cases of ATL were registered in 45 municipalities, rising to 258 municipalities and 4,093 cases from 1986 to 1995; and reaching 385 municipalities and 7,604 cases from 1996 to 2008. Lutzomyia intermedia s.l. was collected in most of the entomological surveys. In the classification of municipalities according to magnitude, 67.5% were observed to have a "small magnitude," 19.2% "moderate magnitude" and 13.3% "high magnitude." The highest incidences of ATL have been restricted to underserved areas close to the Atlantic fo-rest. There was an increase in the number of municipalities with small occurrence of cases and expansion in the area of risk.